PERANCANGAN UI/UX APLIKASI PEMESANAN MAKANAN JEPANG SHOKUAPP PADA RESTORAN XYZ DENGAN PENDEKATAN DESIGN THINKING - Muhammad Mikail Attala; Muhammad Farrel Dimitri; Rully Faizar Ramadhan; Raffiero Yuza Musyaffa; Muhamad Futtuh Hafis Fajri; Yuris Alkhalifi (INTI Nusa Mandiri, 2026)
The rapid growth of Japanese-themed restaurants in Indonesia has created a demand for digital food ordering services that are practical and focused on customer convenience. This study aims to design an alternative UI/UX interface for the “Shoku App,” a prototype self-service ordering app for Restaurant XYZ, using a Design Thinking approach. The design focus is on addressing the challenges of the conventional (manual) ordering process, particularly regarding the menu catalog’s information architecture and inefficient transaction flows. Through the “empathize” and “define” phases, customer needs were synthesized into an Empathy Map and User Persona. In the “ideate” and “prototype” phases, solutions were realized through the creation of wireframes, the standardization of UI guidelines, and the development of an interactive high-fidelity prototype using Figma—which emphasizes a minimalist Japanese-style visual aesthetic and optimizes the shopping cart overlay sheet. The test phase was conducted through usability testing involving 20 respondents using the standardized System Usability Scale (SUS). The evaluation results showed that the Shoku App achieved an average SUS score of 86.63. Based on the SUS interpretation criteria, this result places the app in the “Best Imaginable” category (Grade A+) with an “Acceptable” level of user acceptance. These empirical findings demonstrate that the implementation of a digital interface and simplified navigation effectively provide consumers with an intuitive, efficient, and satisfying self-service transaction experience.